Force Depression in Plantar Flexors Exists Equally in Plantar Flexed and Dorsiflexed Regions - Fukutani, Atsuki; Misaki, Jun; Isaka, Tadao (Frontiers in Physiology, 2017)
Isometric muscle force attained during isometric contractions decreases after active shortening compared to that attained during purely isometric contractions. This phenomenon is called residual force depression. The aim of this study was to examine whether residual force depression occurs in human plantar flexors in both plantar flexed and dorsiflexed region. In addition, the magnitude of fascicle shortening was evaluated because not only muscle force but also fascicle shortening during active shortening are considered to affect force depression. Eleven male subjects were recruited. All muscle contractions were evoked by muscle belly-electrical stimulation. In the reference trials, isometric plantar flexion (PF) was performed at 0° and 15° of PF. In the residual force depression trials, the following two contractions were conducted: 1) muscles were activated isometrically at 15° of dorsiflexion, then actively shortened to 0° of PF (long condition) and 2) muscles were activated isometrically at 0° of PF, then actively shortened to 15° of PF (short condition). Isometric joint torque obtained 4.9 seconds after the onset of contraction was compared between the reference and residual force enhancement trials at the same joint angle to calculate the magnitude of residual force depression. At the same time point, fascicle length and pennation angle were obtained from ultrasonographic images to examine whether the muscle architecture affected residual force depression. As a result, residual force depression was confirmed in both the long and short length conditions (long: 87.1 ± 9.1%, short: 92.1 ± 7.8%) while the magnitude was not different (p = 0.182). The fascicle length and pennation angle were not different between the reference and residual force depression trials (p = 0.291–0.906). These results indicate that residual force depression occurs in the physiological range of motion in the human plantar flexors, and this phenomenon is not related to muscle architecture. In addition, joint angle dependence of the residual force depression was not observed between long and short muscle length conditions.